The Regulatory Governance of Mining Centralization in Indonesia: Assessing Administrative Accountability and the Principle of Prudence - Ayunimas Puspitasari; Muh. Ali Masnun; Naila Adenan (Universitas Negeri Surabaya, 2026)
This study examines the transformation of licensing authority in the mineral and coal mining sector following the enactment of Law Number 2 of 2025 concerning the Fourth Amendment to the Mineral and Coal Mining Law, which centralizes mining licensing under the Central Government through the Risk-Based Business Licensing system implemented via the Online Single Submission (OSS-RBA) platform. Employing normative legal research with statutory and conceptual approaches, this study analyzes the legal construction of licensing authority by applying the doctrine of governmental authority, delegation, and the General Principles of Good Governance, particularly the principles of prudence (zorgvuldigheidsbeginsel) and legal certainty. The analysis demonstrates that although licensing centralization aims to improve regulatory harmonization, investment facilitation, and administrative efficiency, the current institutional design generates significant administrative challenges. The delegation of limited licensing authority to governors is not accompanied by sufficient administrative discretion because the Central Government retains control over norms, standards, procedures, and licensing criteria through the OSS-RBA system. Consequently, regional governments bear administrative responsibility for delegated decisions while possessing only limited authority to determine their substantive content. This institutional arrangement weakens the implementation of the Principle of Prudence by reducing meaningful field verification during licensing and undermines the Principle of Legal Certainty by creating fragmented supervisory responsibilities and delayed administrative enforcement. This study contributes to administrative law scholarship by demonstrating that the effectiveness of licensing governance depends not only on the allocation of authority but also on the institutional consistency between delegated authority, administrative accountability, and supervisory capacity. Accordingly, the study recommends strengthening regional involvement in field verification and restructuring the delegation of supervisory authority to achieve more balanced and accountable mining governance.